Beyond wishful thinking: Explorative Qualitative Modeling (EQM) as a tool for achieving the Sustainable Development Goals (SDGs) - Kai Neumann; Carl Anderson; Manfred Denich (Kiel Institute for the World Economy (IfW), 2017)
The UN's Sustainable Development Goals in their generalized form need to be further reflected in order to identify synergies and trade-offs between their (sub-)targets, and to apply them to concrete nations and regions. Explorative, qualitative cause and effect modeling could serve as a tool for adding crucial factors and enabling a better understanding of the interrelations between the goals, eventually leading to more informed concrete measures better able to cope with their inherent obstacles. This work provides and describes a model that could serve as a template for concrete application. The generalized model already points to some potential ambivalences as well as synergies that can be reflected on using some of the latest theories and concepts from economics and transition research, among other fields. Its first analyses cautiously raise doubts that some possible assumptions behind the original Sustainable Development Goals might overlook some systemic boundaries. For example, an undifferentiated increase of productivity contradicts a lessened environmental impact and need for resources in light of potential planetary boundaries.
Keywords: A19; C19; B49; C38; C69; O10; O19; 330; SDG; transition; sustainability; modeling; explorative; participatory; qualitative; insight matrix; soft factors; feedback loops; evolutionary psychology; know why; decoupling; circular economy; social lab